The healing effects of Ganoderma lucidum on intestinal ischemia-reperfusion damage in rats - Gömeç, Muhammed; Külah, Bahadır; Ercan, Uğur; Şahin, Sevinç (Journal of Surgery and Medicine, 2022)
Background/Aim: Intestinal ischemia-reperfusion (I/R) injury causes serious clinical problems and carries high morbidity and mortality risks. Ganoderma lucidum (GL) is known as an anti-inflammatory immunomodulator and antioxidant. This study aimed to investigate the curative effects of GL on intestinal I/R injury in rats. Methods: Twenty-four Wistar-Albino male rats were randomly divided into three groups. After 30/90 minutes of I/R, intestinal and hepatic tissue examples were histologically examined. Biochemical analysis, serum, intestinal and hepatic tissue malondialdehyde (MDA), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) levels were measured. Results: The I/R group had significantly elevated leukocyte, thrombocyte, serum, and intestinal and hepatic tissue MDA levels compared to the sham group (P < 0.05). Serum, intestinal tissue, and liver tissue SOD levels were significantly lower in the I/R group than in the control group (P < 0.05). In addition, GSH-Px levels measured in serum and liver tissue were lower in the I/R group. However, the use of GL prevented these decreases due to I/R damage. Prior administration of GL considerably alleviated histopathologic changes due to I/R injury in the intestinal and liver tissue samples. Conclusions: Our experimental study showed that I/R injury led to significant oxidative stress by inducing free oxygen radicals in intestinal and hepatic tissues. Serum and tissue MDA, SOD, and GSH-Px levels were considerably useful laboratory parameters in identifying oxidative stress. The protective effects of GL on intestinal I/R injury were promising considering these parameters.